Malacology in Cuba - Morris K. Jacobson (Hello World!, 1972)
Cuba, like the other islands of the Greater Antilles, is unusually rich in land shells, especially landprosobranchs of the families Pomatiasidae (Chondropomidae Annulariidae) and Helicinidae, as well as some pulmonate families like the Urocoptidae and Camaenidae (genera Zachrysia, Polydontes, Pleurodonte and others. But for some reason there was more professional and amateur interest on the part of Cubans themselves in their molluscan fauna than almost any other country in the New World besides the U.S.A.